Chromate Reduction by a Pseudomonad Isolated from a Site Contaminated with Chromated Copper Arsenate - McLean, Jeff (American Society for Microbiology, 2001)
A pseudomonad (CRB5) isolated from a decommissioned wood preservation site reduced toxic chromate [Cr(VI)] to an insoluble Cr(III) precipitate under aerobic and anaerobic conditions. CRB5 tolerated up to 520 mg of Cr(VI) liter(−1) and reduced chromate in the presence of copper and arsenate. Under anaerobic conditions it also reduced Co(III) and U(VI), partially internalizing each metal. Metal precipitates were also found on the surface of the outer membrane and (sometimes) on a capsule. The results showed that chromate reduction by CRB5 was mediated by a soluble enzyme that was largely contained in the cytoplasm but also found outside of the cells. The crude reductase activity in the soluble fraction showed a K(m) of 23 mg liter(−1) (437 μM) and a V(max) of 0.98 mg of Cr h(−1) mg of protein(−1) (317 nmol min(−1) mg of protein(−1)). Minor membrane-associated Cr(VI) reduction under anaerobiosis may account for anaerobic reduction of chromate under nongrowth conditions with an organic electron donor present. Chromate reduction under both aerobic and anaerobic conditions may be a detoxification strategy for the bacterium which could be exploited to bioremediate chromate-contaminated or other toxic heavy metal-contaminated environments.